2022
DOI: 10.1109/tbme.2021.3092437
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Probe for Sentinel Lymph Node Harvesting Using Magnetic Nanoparticles

Abstract: Sentinel lymph node harvesting is an essential step in the surgical treatment of a growing number of malignancies. Various techniques are available to facilitate this purpose. The present study reports a new laparoscopic technique for lymph node harvesting using magnetic nanoparticles containing a superparamagnetic iron-oxide core and dextran coating. This study assesses the clinical relevance of the prototype and provides input for further technological development on the way to clinical implementation. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…During operation, tissues in which SPIONs are accumulated can be detected using a handheld magnetometer [33]. A recent study reported the development of a laparoscopic differential magnetometer probe, which showed promising results in terms of intraoperative SLN localization [34]. Although it is a relatively new method, the available data indicate its high efficiency in detecting SLNs.…”
Section: Markers and Imaging Methodsmentioning
confidence: 99%
“…During operation, tissues in which SPIONs are accumulated can be detected using a handheld magnetometer [33]. A recent study reported the development of a laparoscopic differential magnetometer probe, which showed promising results in terms of intraoperative SLN localization [34]. Although it is a relatively new method, the available data indicate its high efficiency in detecting SLNs.…”
Section: Markers and Imaging Methodsmentioning
confidence: 99%
“…The complete LapDiffMag system consists of three main parts [11,14]: a set of excitation coils, a detection probe, and a control unit (Fig. 1).…”
Section: A Designmentioning
confidence: 99%
“…The detection probe consist of two coils to detect the magnetic signal and two coils to compensate for the magnetic field generated by the excitation coil. The probe is designed to be operated by a laparoscopic surgeon and already tested with a clinical setting in mind [11]. The control unit consists of multiple parts: two power supplies, a transformer, a series resonant circuit, safety equipment, and a data acquisition system.…”
Section: A Designmentioning
confidence: 99%
See 2 more Smart Citations